Development of interregional tools for predictive modeling of spatial proportions of economy - Boris Viktorovich Melent'ev (European Regional Science Association (ERSA), 2014)
Attention invited to the most workable cross sectoral interregional models relating to application tools of integrated analysis and forecasting (planning) where scenarios are defined by physical output indicators dependent on material, labor and capital costs together with objective production limits. These models date back to input-output balances and Input-Output models without regions with discrete time over fixed years in a consistent task within the period under review (L. V. Kantorovich, V. L. Makarov, A. A. Shirov and others). The specifics of interregional (spatial) models is that they contain sets describing interregional product supplies and conditions for the development of regional economies. An individual prediction of the economic development of a territory is required for each subject. Interregional calculation sare complex, because regional economies and ultimate consumption are considered together, which ensures regional predictions with mutually balanced external connections for each region. In addition, ultimate performance indices are backed with a necessary production sectoral base spread across different regions, in which particular socioeconomic decisions are made. The following step of the development of cross sectoral tools is the development of interregional financial long term balances "Payments-Incomes". The basis of these balances are the mentioned models of input-output balance (Input-Output) and optimization interregional models of physical composition. Classical optimization cross sectoral (product) models are not yet adapted for the development of detailed applied forecast of regional prices and compound financial balances over the territories as in general the dual appraisals for interregional models have no characteristics of current prices. The financial balance model of each region reflects the financial relations of a region's economic entities with each other and their relations with other regions, including foreign countries. These entities include the population that realizes economic activities, earns income, and undertakes expenses in this territory and the region's industries and banking, credit, state, and other organizations. In terms of the content, a regional financial balance is an instrument (document) in which a region's income and expenses are indicated, as well as the flows of payments of its economic entities for products and services bought and sold and other financial transactions.
Keywords: O21; R11; 330; methods of regional analysis; interregional financial balance